The implementation of new technologies in healthcare organizations: Cultural-historical activity theory - Masovic, Jasmina (Oeconomica Jadertina, 2024)
The implementation of new technologies in healthcare leads to the emergence of new practices that diverge from traditional medical procedures. Existing scientific literature observes that new technologies often contradict conventional treatment methods, thereby posing a threat to existing divisions of labor and responsibilities among healthcare professionals and their medical domains. It is expected that tensions and conflicts arising from these contradictions hinder the implementation of new technologies and procedures in healthcare organizations. However, this article challenges such assumptions, arguing that conflicts between old and new practices or among practices of different medical domains are actually one of the main drivers of innovation. Cultural-historical activity theory (Engeström, 1987; 2001; Blackler, 2009) promotes a dialectical approach to researching the implementation of new technologies in organizations. It contends that consensus between old and new, or between domain-specific practices is not necessary for new technologies to be successfully implemented, provided there is a shared goal of activity. On the contrary, contradictions and tensions between different ways of working are considered regular characteristics of activity systems during the introduction of new technologies in organizations. This article presents the results of a long-term case study on a hospital’s implementation of a new technology called Transcatheter Aortic Valve Implantation (TAVI) which is a minimally invasive cardiac procedure. The newly introduced procedure enables the treatment of previously inoperable patients suffering from aortic valve stenosis. During the five-year ethnographic study of its implementation, numerous contradictions and difficulties in the progress of this innovation were documented. By applying cultural-historical activity theory to the case, various contradictions initially thought to impede its progress were identified. However, it turns out that the expansion of doctors' activities and the transformation of aortic stenosis treatment arose precisely from these contradictions. Although generalizations cannot be drawn from case studies, this example demonstrates the utility of using cultural-historical activity theory in researching the modernization of healthcare organizations. Therefore, this article contributes to the development of new theoretical approaches and methods, urging researchers and theorists of technology implementation to re-examine the current understandings of these processes.
Keywords: new technology implementation; technological change; healthcare organizations; interdisciplinary work; cultural-historical activity theory; practice-based studies